IMAGINING SOCIAL JUSTICE THROUGH THE INTERNET AND BEYOND - Eckert, Stine; Deller, Ruth; Croeser, Sky; Donovan, Gregory (AoIR Selected Papers of Internet Research, 2015)
From scholarly discussions to mainstream publications, there is a growing understanding that theoretical, largely academic conceptions of social justice are in many ways disconnected from the people, practices, and projects actively pursuing justice today. At the same time, concepts with rich theoretical histories have emerged as key terms and battleground ideas for discussions of social justice online—including, for example, renewed discussions of feminism, social and economic class, intersectionality, and familiar liberal ideals of liberty and equality. In an effort to overcome the distance between social justice as a target of scholarly inquiry and the real concerns of social justice movements, contributions to this panel critically engage issues of social justice both within and across different applied online contexts and practices. They articulate various possibilities and limits for imagining a more just world through the communicative and political affordances of the Internet and other advanced information and communication technologies (ICTs). In the first paper, the experiences of women bloggers are marshaled to challenge established theories of the public sphere that might otherwise fail to account for the voices of those writing about the politics of women, family and maternity. In doing so, we are encouraged to imagine more broadly inclusive democratic debates. In the second paper, the idea of the “social justice warrior”—a term that has emerged online as a way to marginalize individuals deemed excessive in their pursuit of inclusion and represetnation—and its implications for social justice discourse broadly are discussed. In this case, we are presented with an example of hegemonic resistance to expressions and imaginaries of justice enabled by the affordances of certain online platforms for political and progressive expression. In the remaining papers, established political frames for addressing injustice are critiqued and countered. In the third paper, the appeal by both activists and academics to discourses familiar to the liberal democratic state—including rights and liberties—is challenged and shown to limit our collective imaginaries of social justice online. In the final paper, neoliberal policies of privatization, gentrification, and dataAdriven “smart urbanism” and their failure to improve or respond to local injustices faced by marginalized citizens specifically black and brown youth) are laid bare. The author— drawing on the successes and failures of four different “smart” initiatives in the New York City area—responds by developing an alternative framework grounded not in quantitative analyses but, rather, in empathy and qualitative study. Combined, these papers explore some of the ways in which theoretical and empirical scholarly investigations can open up new paths for thinking about social justice with regard to platforms, communities, or practices—online and beyond. They attend to the ways in which broader conversations or movements—for example, those oriented around the efforts of Western women bloggers, rightsAbased liberatory language, or resistance to “smart” urban policies—challenge or force us to reconsider the ways in which we conceive of and discuss values relevant to social justice, like inclusion, fairness, and equality. Finally, the panel members all share an awareness of the fact that this panel is articulated in a way familiar to those embedded in an academic or research intensive context. We recognize that any conversation about social justice issues online is incomplete without the inclusion of a wider range of voices, from activists to organizers to advocates. To that end, we intend this panel as one part of a larger series of proposed sessions engaging social justice issues and the Internet, some of which go beyond traditional academic frameworks. Here, however, we use the standard “panel of papers” frame in an effort to show how even conventional formats can generate productive or liberatory discussions. Ultimately, it is our position that more conversations—within and across various contexts—are better than fewer when confronting pressing issues of discrimination, bias, fairness, and equality today.